Duplication, Fragmentation, and Overlapping: Linguistic Landscape Dynamics of Tourist Attractions in Gianyar, Bali - Sang Ayu Isnu Maharani; Ketut Artawa; Ida Ayu Made Puspani; Ketut Widya Purnawati (Pusat Kajian Bali Universitas Udayana, 2025)
With its rich array of tourist attractions, the Gianyar region in Bali features numerous outdoor signs that contribute to its complex linguistic landscape. This study investigates linguistic landscape patterns and text typologies using a qualitative research method based on observation, note-taking, and photography. The analysis follows the linguistic landscape framework by Landry and Bourhis (1997) and the multilingual text typology by Reh (2004). Findings reveal that the linguistic landscape of Gianyar’s tourist sites falls into cultural, village, museum, nature, and man-made categories. Outdoor signage patterns are classified as top-down and bottom-up. Top-down signs predominantly feature duplicating and fragmentary text typologies, while bottom-up signs incorporate duplicating, fragmentary, and overlapping structures. These findings enhance the understanding of the linguistic landscape in Gianyar, providing insights into its multilingual environment, particularly within public spaces and tourist destinations.